Surgical treatment of intrahepatic cholangiocarcinoma: a retrospective study of 104 cases - Xun, Xiao-Dong (Cancer Biol Med, 2016)
OBJECTIVE: To explore the clinicopathological features, surgical treatment techniques, and prognostic risk factors of intrahepatic cholangiocarcinoma (ICC). METHODS: A total of 104 ICC cases were collected from January 2008 to December 2013 at Tianjin Medical University Cancer Institute and Hospital and divided into the hepatic hilum lymphadenectomy (HLL, 21 cases), extended hepatic hilum lymphadenectomy (EHLL, 12 cases), and non-lymphadenectomy (NL, 71 cases) groups. The clinical data of the patients were retrospectively analyzed, and the prognostic differences were compared among different groups. RESULTS: The 1-, 2-, and 3-year overall survival (OS) rates of all cases were 72.1%, 56.1%, and 43.7%, respectively. The median survival duration was 34 months. The 1-, 2-, and 3-year OS rates of the HLL group (42.9%, 28.6%, and 28.6%, respectively) were significantly lower than those of the NL group (78.9%, 62.5%, and 47.8%, respectively). Meanwhile, the 1-, 2-, and 3-year OS rates of the EHLL group (75.0%, 56.1%, and 33.3%, respectively) were not significantly different from those of the other two groups. Univariate analysis showed that age, gender, American Joint Committee on Cancer (AJCC) stage, differentiation, ferritin (Fer), carbohydrate antigen19-9 (CA19-9) and carcinoembryonicantigen (CEA) levels, lymph node metastasis (LNM), and lymph node dissection (LND) were prognostic factors for the long-term survival of ICC. Meanwhile, multivariate analysis revealed that age, AJCC stage, differentiation, Fer levels, and LNM were independent risk factors for survival. CONCLUSIONS: ICC patients will not benefit from lymphadenectomy in the absence of LNM. However, systematic lymphadenectomy may improve ICC outcomes if the location of lymphatic metastasis is known. Age, AJCC stage, differentiation, Fer level, and LNM are independent risk factors for survival in ICC.